An examination of the prevention of cable theft from Eskom - Govender, Remone (Acta criminologica, 2017)
Cable theft is currently considered a significant problem, globally. The Eskom statistical figures indicate that cable theft creates a massive problem for service delivery and places a vast amount of pressure on its financial resources. Cable theft is highlighted on various platforms within Eskom’s business operating units and while efforts for increased security and protection measures are in place, these measures appear to be inadequate to prevent it. This study investigated the extent of cable theft at Eskom and examined what actions Eskom and private security personnel should undertake to prevent it. This study further determined what action steps need be taken by Eskom’s internal security management team and those responsible for the capturing of all relevant information related to it, in order to prevent any form of cable theft. This research made four key contributions to the subject: (i) A new Eskom security structure was proposed, (ii) a newly designed Eskom training curriculum framework was designed for all private security personnel working at Eskom facilities, (iii) proposed changes to Eskom’s CURA1 system were made, and (iv) proposed changes were suggested for Eskom’s internal ENECC2 cable theft reporting system.